Electronic structure and spectra of (Cu2O)n–H2O complexes. Issue 1 (12th November 2014) - Petsalakis, Ioannis D.; Theodorakopoulos, Giannoula; Whitten, Jerry
Abstract : (Cu2 O) n clusters form nanobarrels with a square mesh surface structure. Low-lying charge-transfer electronic excited states of (Cu2 O) n –H2 O are determined. Abstract : Density functional theory calculations have been employed to determine optimized geometries for different (Cu2 O) n clusters for n = 1 to 6, 12 and 18. The results show the formation of (Cu2 O) n rings for n ≥ 2, while (Cu2 O) n nanobarrels have been determined for n = 12 and for n = 18. Adsorption of H2 O on the (Cu2 O) n clusters occurs preferentially by interaction of the water O with outer Cu atoms. Absorption spectra calculated by time dependent density functional theory show that in all cases charge-transfer excitations from occupied orbitals of the (Cu2 O) n cluster to a Rydberg orbital of H2 O contribute to the character of the singlet excited states calculated at energies starting at about 2.6 eV, with increasing contribution found at higher excitation energies. Configuration interaction calculations on selected (Cu2 O) n –H2 O complexes determine charge-transfer excitations to contribute significantly to excited states lying at 4.6–6.2 eV above the ground state.